2018
DOI: 10.1038/s41598-018-19934-6
|View full text |Cite
|
Sign up to set email alerts
|

Grey matter OPCs are less mature and less sensitive to IFNγ than white matter OPCs: consequences for remyelination

Abstract: Multiple sclerosis (MS) is a chronic inflammatory disease characterized by the formation of demyelinated lesions in the central nervous system. At later stages of the disease repair in the form of remyelination often fails, which leads to axonal degeneration and neurological disability. For the regeneration of myelin, oligodendrocyte progenitor cells (OPCs) have to migrate, proliferate and differentiate into remyelinating oligodendrocytes. Remyelination occurs faster and is more extensive in grey matter (GM) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 71 publications
2
47
0
Order By: Relevance
“…One study showed that only approximately 20% of patients are thought to remyelinate to some extent [3], but the mechanisms separating successful and failed remyelination are not well known [7], even when the progenitors of myelin-producing cells are present at the sites of injury [8,9]. For OPCs to contribute to remyelination, they likely must migrate to the sites of injury, proliferate, and differentiate into OLs [10]. Each of these processes can be inhibited by cytokines (e.g., IL-6, IL-17, osteopontin, IFNγ, TNFα), chemokines (e.g., CXCL1, CXCL2, CXCL10, CXCL11), cytolytic proteins (e.g., lymphotoxin-a and perforin), and signaling factors (e.g., astrocyte-derived endothelin-1 (ET-1), all of which are known to be present at demyelinated areas [11][12][13][14][15][16], thereby establishing a potentially challenging environment for repair.…”
Section: Introductionmentioning
confidence: 99%
“…One study showed that only approximately 20% of patients are thought to remyelinate to some extent [3], but the mechanisms separating successful and failed remyelination are not well known [7], even when the progenitors of myelin-producing cells are present at the sites of injury [8,9]. For OPCs to contribute to remyelination, they likely must migrate to the sites of injury, proliferate, and differentiate into OLs [10]. Each of these processes can be inhibited by cytokines (e.g., IL-6, IL-17, osteopontin, IFNγ, TNFα), chemokines (e.g., CXCL1, CXCL2, CXCL10, CXCL11), cytolytic proteins (e.g., lymphotoxin-a and perforin), and signaling factors (e.g., astrocyte-derived endothelin-1 (ET-1), all of which are known to be present at demyelinated areas [11][12][13][14][15][16], thereby establishing a potentially challenging environment for repair.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneity among oligodendroglial progenitor cells (OPCs) has previously been related to their gray (GM) or white matter (WM) localization in the central nervous system (CNS; (Lentferink, Jongsma, Werkman, & Baron, 2018;Vigano, Möbius, Götz, & Dimou, 2013)). Based on single cell sequencing data, this information has recently been expanded describing regional differences among oligodendroglial cells (Marques et al, 2016) as well toward disease-specific lineages upon demyelination (Falcao et al, 2018;Jäkel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This is primarily visible in type 1 leukocortical lesions. In these gm and wm spanning lesions, the gm area shows greater remyelination efficiency, which may be a reflection of lower astrocyte reactivity, higher number of cells of the oligodendrocyte lineage, regional heterogeneity of OPCs, and decreased intralesional ECM deposition 10,12,76 . The presence of fibronectin aggregates in gm MS lesions remains to be determined, but based on the less inflammatory character of gm lesions 75 , the absence of fibronectin immunoreactivity in marmoset gm EAE lesions 77 and our present findings, it is tempting to hypothesize that in gm MS lesions less remyelination-impairing fibronectin aggregates are formed than in (chronic) wm MS lesions.…”
Section: Discussionmentioning
confidence: 98%
“…All methods were carried out in accordance with national and local experimental animal guidelines and regulations. Primary gm rat astrocytes of either sex were isolated from the neonatal cortex and wm astrocytes from neonatal non-cortical parts, which mainly consist of wm, by a shake off procedure and cultured as described 19,59,76 . Astrocytes were cultured at a density of 1 × 10 6 cells/10 cm-dish, 50,000 cells/13-mm poly-L-lysine (5 µg/ml)-coated coverslip, or 20,000 cells/8-well Permanox chamber slide.…”
Section: Methodsmentioning
confidence: 99%